Karelia lost or won – materialization of a landscape of contested and commemorated memory - Petri J. Raivo (Geographical Society of Finland, 2004)
The national memory is often signified by means of monuments erected in the landscape, while commemorative historical sites always carry a story from the past, and it is not a matter of indifference how this story is told. Karelia, and particularly the areas of the Karelian Isthmus, the shores of Lake Ladoga and the Karelian Borderlands that were ceded to the Soviet Union as a consequence of the Second World War, are places where the commemorative sites have been objects of dispute for the last 60 years. Memories of Finnish Karelia have been erased, transformed and brought to life again: erased and transformed by the post-war masters of the area, for whom it was ideologically most appropriate to replace the Finnish narrative with one telling of victory in the Great Patriotic War and alluding to new sites commemorating the region’s Russian history. The more recent revival of Finnish memories has been brought about not only by the Finns but also by Russians who have wished to tell the presentday inhabitants of Karelia about the forgotten and suppressed details of its more recent history.